PENERAPAN SKEMA BUY THE SERVICE PADA ANGKUTAN PERDESAAN DI KABUPATEN KOTABARU (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
The availability of public transportation is a major factor in facilitating, supporting, and enhancing development both at the regional and national levels as well as the welfare of the people. The transportation sector in Kotabaru Regency has several problems with public transportation services which are currently not optimal. Broadly speaking, the reasons for the low public interest in public transportation are that the services provided are still far from expectations and are not in accordance with minimum service standards, such as the vehicles used do not pay attention to safety aspects, there is no definite service schedule and information related to public transportation is not yet available. easily accessible. One of the steps that can be taken by the Kotabaru Regency government is to establish a policy or program called "Buy The Service" to improve services on rural transportation, especially on the Kotabaru-Sambuluan and Kotabaru-Berangas routes in accordance with the objectives of this study. The data used are primary data obtained from survey results and secondary data obtained from relevant agencies. Based on data collection and analysis results, the actual demand is 239 people/day trips, for the potential demand for public transportation with interest in moving private vehicles is 2.3%, namely 7356 people/day trips. The operation of Buy The Service in Kotabaru Regency is served by minibus type with a capacity of 16 people with the need for the Kotabaru-Sambuluan route fleet of 27 vehicles and the Kotabaru-Berangas route as many as 31 vehicles. In order to attract people to take public transportation, a full subsidy will be applied for a predetermined period. The cost required to purchase a transportation service is Rp 16,465,693,568.54 per year. ABSTRAKTersedianya angkutan umum menjadi faktor utama dalam memperlancar, menunjang, dan meningkatkan pembangunan baik di tingkat daerah maupun nasional serta kesejahteraan rakyat. Sektor transportasi pada Kabupaten Kotabaru memiliki beberapa permasalahan pelayanan angkutan umum yang saat ini belum optimal. Secara garis besar alasan yang menjadi penyebab rendahnya minat masyarakat terhadap angkutan umum yaitu pelayanan yang diberikan masih jauh dari harapan dan belum sesuai dengan standar pelayanan minimal, seperti kendaraan yang digunakan kurang memperhatikan aspek keselamatan, belum adanya jadwal pelayanan yang pasti dan informasi terkait angkutan umum belum bisa diakses dengan mudah. Salah satu Langkah yang bisa dilakukan oleh pemerintah Kabupaten Kotabaru adalah menetapkan suatu kebijakan atau program yang disebut dengan “Buy the Service” guna memperbaiki pelayanan pada angkutan pedesaan terutama pada trayek Kotabaru-Sambuluan dan Kotabaru-Berangas sesuai dengan tujuan dari penelitian. Data yang digunakan merupakan data primer yang didapatkan dari hasil survei dan data sekunder yang didapatkan dari instansi terkait. Berdasarkan pengumpulan data dan hasil analisis diperoleh permintaan aktual sebesar 239 perjalanan orang/hari, untuk permintaan potensial angkutan umum dengan minat pindah kendaraan pribadi sebesar 2,3% yaitu 7356 perjalanan orang/hari. Pengoperasian Buy the Service di Kabupaten Kotabaru dilayani dengan jenis minibus dengan kapasitas 16 orang dengan kebutugan armada trayek Kotabaru-Sambuluan sebanyak 27 kendaraan dan trayek Kotabaru-Berangas sebanyak 31 kendaraan. Guna menarik minat masyarakat untuk naik kendaraan umum akan diterapkan subsidi penuh selama periode yang telah ditentukan. Biaya yang dibutuhkan untuk membeli layanan angkutan sebesar Rp 16.465.693.568,54 per tahun.